Social Determinants of Adherence to Treatment for Tuberculosis Infection and Disease Among Children, Adolescents, and Young Adults: A Narrative Review - Leddy, Anna M.; Jaganath, Devan; Triasih, Rina; Wobudeya, Eric; Bellotti de Oliveira, Marcia C.; Sheremeta, Yana; Becerra, Mercedes C.; Chiang, Silvia S. (Journal of the Pediatric Infectious Diseases Society, 2022)
Global efforts to eliminate tuberculosis (TB) must address the unique barriers that children (ages 0 through 9 years) and adolescents/ young adults (AYA; ages 10 through 24 years) face in adhering to treatment for TB infection and disease. We conducted a narrative review to summarize current knowledge on the social determinants of treatment adherence among these age groups to guide efforts and policy to address their unique needs. Our findings revealed that research on TB treatment adherence among children and AYA is still in its nascent stage. The current literature revealed structural/community-, health system-, household-, and individual-level factors that influence treatment adherence and varied with developmental stage. There is a need to develop multilevel interventions to address the unique challenges that children and AYA face in adhering to TB treatment
Keywords: tuberculosis; medication adherence; adolescents; children